PENGARUH MOTIVASI DAN PELATIHAN TERHADAP KINERJA PARA PELAKU UMKM BINAAN LAZISMU PEKANBARU - SUKRIANI, NURUL (Jurnal Daya Saing, 2018)
This study aims to analyze performance of participants UMKM which was built by Lazismu Pekanbaru, by using motivation and training variables, to analyze its effect on the performance of the participants. The population in this study are all participants of UMKM which amounted to 38 people, and the sample involves the entire population, using the census method. Data collected by questionnaire method is by giving questionnaire directly to the respondents.Data analysis technique used is multiple linear regression analysis which operated through program SPSS 16 for Windows. The results showed that both simultaneously and partially motivation and training variables significantly influence the performance of the participants UMKM built by Lazismu Pekanbaru. Keywords: Motivation, Training, Performance